Pelatihan dan Pendampingan Lean Management dalam Memberikan Value Added Service pada Usaha Dagang Pertanian - Amrussalam; Eko Supriastuti; Muhammad Nursan; Rahmawati; Ary Apriyani; Sulaimansyah (Universitas Mataram, 2022)
Lean management is used as a management system and methodology to be able to organize and manage the management of the Agricultural Trading Business 'Hj. NURIMAN' against waste that does not add value to its trade production. The goal to be achieved in this community service program is provide assistance on the implementation of Lean Management by using the 5S concept to eliminate waste and improve services in providing value-added services to farmers. The result of this community service program able to eliminate of waste in the trading activities 'Hj. NURIMAN' and increasing services to farmers which include facilitating supplementary services and enhancing supplementary services